-7=5+3a-6a

Simple and best practice solution for -7=5+3a-6a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7=5+3a-6a equation:


Simplifying
-7 = 5 + 3a + -6a

Combine like terms: 3a + -6a = -3a
-7 = 5 + -3a

Solving
-7 = 5 + -3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
-7 + 3a = 5 + -3a + 3a

Combine like terms: -3a + 3a = 0
-7 + 3a = 5 + 0
-7 + 3a = 5

Add '7' to each side of the equation.
-7 + 7 + 3a = 5 + 7

Combine like terms: -7 + 7 = 0
0 + 3a = 5 + 7
3a = 5 + 7

Combine like terms: 5 + 7 = 12
3a = 12

Divide each side by '3'.
a = 4

Simplifying
a = 4

See similar equations:

| 72x^4-50x^2=0 | | -18=-2n-4n | | 10x+-3=4x-21 | | 11x-3(6-3x)= | | 3x+4(3x-5)=130 | | 3.98i+11.94=23.88 | | 3x+15=2x-5 | | 8-(6-7)=0 | | 8(x+4)=-64 | | 3y+2y=2y-5x | | X+m=no+rq | | 7x-32-9x=8 | | Y=3x^5+3x^3-60x | | -6-(6-6p)=0 | | 4(4-4x)+4=-2x+2-14x | | 5-9+x=65 | | -4=4(3-b) | | 6x+3(4x+2)=96 | | -4x+6=6x+16 | | 9x-1=2x-12 | | -14=3x+10 | | 3x*-5=4x*-2 | | 10+x-6=2 | | 3h-6=24 | | 6i-4=2i+24 | | 15x+3x-4=14whatisx | | 3x+5x+5=11+10x+6 | | 6(x+3)+7-x=4x(x+3) | | S-15=15.19 | | 8X-14=7X+9 | | 9(x-2)=72 | | 3(2x-5)+6=4x+7 |

Equations solver categories